(untitled) (Jahangirnagar University Journal of Biological Sciences, 2018)
Soil: Plant nutrient status in naturally regenerated garjan (Dipterocarpus turbinatus Gaertn.) seedlings of 3, 9, 15, 21, 27 and 33 months old were studied in twelve stands of three sites on late and early monsoon during 1994 to 1995 in Dulahazara garjan forest of Cox’s Bazar forest division. Soil samples were collected from two profiles (i.e. top soil and sub soil) of twelve stands in three sites. Soil moisture content, pH, texture, electrical conductivity, cation exchange capacity, organic carbon, total N and available P, K, Ca, Mg, Mn and Fe were determined. Soils were found to be silty loam to sandy loam with an average pH of 5.06. The average values of organic carbon and cation exchange capacity were 0.74% and 6.23 meq/100g respectively. The soils were poor in total nitrogen (689 μg g-1) and the average values of available mineral nutrients such as P, K, Ca, Mg, Mn and Fe in soil were 3.15, 53, 40, 47, 36 and 0.94 μg g-1, respectively. The soil in site -S2 appeared to be more fertile than those of site-S1 and site-S3. The average values of N, P, K, Ca, Mg, Mn and Fe in leaf- bud were found to be 1.80, 0.13, 0.94, 0.72, 0.23, 0.06 and 0.014% respectively. Leaf-bud nutrients showed a marked variation both with seasons as well as ages. Leaf-bud of late monsoon contained higher concentrations of P, Mg and Ca compared to leaf-bud of early monsoon which contained higher concentrations of N, K and Fe. Nutrient cycling in soil:leafbud system of regenerated garjan seedling of 3-33 months old varied with seasons and ages. The present study reveals that concentrations of Mn were significantly correlated between leaf-bud and soil whereas P showed the negative correlation indicating that in spite of low quantity of P in the soil, leaf bud had higher quantity. Jahangirnagar University J. Biol. Sci. 7(2): 79-88, 2018 (December)